Marketing Strategies for Cassava Chips to Enhance Competitiveness in the Local Market at Rizky Jaya Sempurna SME - Syarif Hidayatullah; Ahmad Soleh; Ida Ayu Made E. G. (Jurnal Ekonomi Islam, Akuntansi, dan Manajemen, 2026)
In the face of increasingly fierce competition in the cassava chip industry, strengthening competitiveness is crucial for business sustainability and growth, especially in the local market. One effective approach to improving competitiveness is to conduct a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis. This analysis provides a clear picture of the strengths, weaknesses, opportunities, and threats faced by cassava chip producers in the local market. This study aims to determine the marketing strategies for Rizky Jaya Sempurna MSME home industry cassava chips in the local market using the SWOT analysis method with four basic components, namely Strengths, Weaknesses, Opportunities, and Threats, with a sample of 24 respondents. The results of the study show that the IFAS and EFAS score recapitulation obtained from the IFAS matrix indicates strength and weakness factors from the 0.474 quadrant. This indicates that the cassava chip business of the Rizky Jaya Sempurna MSME is in a strong internal position. Meanwhile, the EFAS matrix shows that the opportunity and threat factors indicate a quadrant of 0.312. This indicates that the cassava chip product of Rizky Jaya Sempurna MSME is in a favorable situation, with the company gaining various opportunities from outside and strength from within.